PENGARUH PROMOSI KESEHATAN REPRODUKSI TERHADAP TINGKAT PENGETAHUAN SISWA DI SMA KALIMANTAN BARAT - Sutriana Anastasia; Justina Purwarini; Sada Rasmada (Jurnal Ilmiah Keperawatan, 2020)
Background: Adolescence is a transition from childhood to adulthood, during this time many complex problems occur so that they must be able to solve these problems to become a quality next generation. Problems that can occur in adolescence include reproduction health problems such as unwanted pregnancy, abortion, and sexually transmitted diseases (STDs). One strategy that can be used to increase adolescent knowledge is to provide health promotion. Adolescents begin to explore their thoughts and find out about the changes that occur in themselves. Objective: This study aims to determine the effect of reproductive health promotion on the level of student knowledge in Mamiamas Ngabang High School. Method: This study is a quantitative study with a quasi-experimental method with one group pre-test-post test design, with 145 respondents. Results: From the results of the t-test there are differences in the level of knowledge between before and after health promotion (p <.005) with significance .000, based on the results of the magnitude of p obtained, it was concluded that there was an influence on the promotion of reproductive health on the level of student knowledge about reproductive health at Maniamas Ngabang High School. Recommendation: providing regular health promotion to provide information at a further level can increase adolescent awareness about reproduction health.